N-ethoxycarbonylpyrene- and perylene thioamides as building blocks in the synthesis of efficient color-tunable 4-hydroxythiazole-based fluorophores. (January 2019) - Witalewska, Marzena; Wrona-Piotrowicz, Anna; Zakrzewski, Janusz
Abstract: N -Ethoxycarbonylpyrene- and perylene thioamides were used as building blocks in the synthesis of a variety of fluorescent dyes bearing thioimidate, 4-hydroxythiazolyl, 4-methoxythiazolyl and thiazole-4-one moieties, and an ester function. The synthesized compounds in DMSO solutions display fluorescence in the range of 412–672 nm with quantum yields 0.1–0.88. 2-(Pyrene-1-yl)-5-ethoxycarbonyl-4-hydroxythiazole and 2-(perylene-3-yl)-5-ethoxycarbonyl-4-hydroxythiazole show dual fluorescence resulting from the excitation of the neutral fluorophore and the corresponding enolate anion formed via excited state proton transfer (ESPT). As a result of ESPT the former fluorophore emits white light (CIE coordinates: 0.33, 0.36). The pyrenyl and perylenyl substituted 5-ethoxycarbonyl-5-methyl-( 5H )-thiazole-4-ones displayed the highest emission efficiency (ΦF ∼0.9) and emission maxima at 503 nm and 626 nm, respectively. The observed solvatochromism suggests that in this case emission originates from intramolecular charge transfer (ICT) excited states. Highlights: Thioimidates, 4-hydroxythiazoles, their salts and thiazol-4-ones bearing pyrenyl and perylenyl groups at C-2 were synthesized. The synthesized compounds emit fluorescence covering practically the entire visible region. The synthesized 4-hydroxythiazoles in DMSO display dual fluorescence resulting from excited state proton transfer (ESPT). As a result of ESPT pyrenyl-substituted 4-hydroxythiazole emits white light (CIE chromaticity coordinates: 0.33; 0.36). The synthesized thiazol-4-ones proved very efficient emitters (ΦF ∼0.9 in DMSO) with λ max at 503 nm and 626 nm, respectively.